Campaigning on Campus: Student Islamic Societies and Counterterrorism. (2nd December 2017) - Choudhury, Tufyal
ABSTRACT: Cooperation in counterterrorism policing increases when communities can be confident that legislation and policy is not implemented in an arbitrary or discriminatory fashion: the ability to challenge executive overstretch, abuse, or misapplication of powers is vital for maintaining procedural justice. Through examining the experiences of the Federation of Student Islamic Societies, one of the oldest British Muslim civil society organizations, we see how key structural features of the counterterrorism legal and policy framework—the wide definition of terrorism, the broad discretion in the use of stop and search powers at ports, and the expansion of Prevent into the opaque terrain of nonviolent extremism—undermine cooperation.